Evaluation of N-terminal pro-atrial natriuretic peptide and Soluble ST2 as Predictors for Cardiovascular Diseases in Patients with Type 2 Diabetes in Al-Basra, Iraq - Jabber, Haider; Charfeddine, Bassem; Abbas, Hamed (Journal of Biomedicine and Biochemistry, 2024)
Background Cardiovascular disease (CVD) is an umbrella term for a group of illnesses that have an adverse effect on the cardiovascular system. Diabetic cardiomyopathy and atherosclerotic CVD, which may cause heart failure via myocardial infarction and chronic pressure overload, are preva- lent metabolic disorders associated with type 2 diabetes mellitus (T2DM). The Aim Examine the connection between the amount of serum N- terminal pro-atrial natriuretic peptide and Soluble ST2 in patients with type 2 diabetes who have cardiovascular diseases. Material and Method Examine the connection between the amount of serum N-terminal pro-atrial natriuretic peptide and Soluble ST2 in pa- tients with type 2 diabetes who have cardiovascular diseases. Results The research findings demonstrated a rise in the N-terminal pro-atrial natriuretic peptide levels in patients with cardiovascular disease (CVD) and diabetes mellitus (DM) compared to those with just DM and the control group. Furthermore, there was a notable disparity in con- centrations across the different study groups, with a p-value of less than 0.0001. Furthermore, the findings of this research demonstrated a rise in the concentration of Soluble ST2 in patients with both cardiovascular dis- ease (CVD) and diabetes mellitus (DM) as compared to those with just DM and the control group. There was a notable disparity in the levels of Soluble ST2 across the different groups in the research (p-value